Continuous flame aerosol synthesis of carbon-coated nano-LiFePO(4) for Li-ion batteries - Waser, Oliver (2011)
Core-shell, nanosized LiFePO(4)-carbon particles were made in one step by scalable flame aerosol technology at 7 g/h. Core LiFePO(4) particles were made in an enclosed flame spray pyrolysis (FSP) unit and were coated in-situ downstream by auto thermal carbonization (pyrolysis) of swirl-fed C(2)H(2) in an O(2)-controlled atmosphere. The formation of acetylene carbon black (ACB) shell was investigated as a function of the process fuel-oxidant equivalence ratio (EQR). The core-shell morphology was obtained at slightly fuel-rich conditions (1.0 < EQR < 1.07) whereas segregated ACB and LiFePO(4) particles were formed at fuel-lean conditions (0.8 < EQR < 1). Post-annealing of core-shell particles in reducing environment (5 vol% H(2) in argon) at 700 °C for up to 4 hours established phase pure, monocrystalline LiFePO(4) with a crystal size of 65 nm and 30 wt% ACB content. Uncoated LiFePO(4) or segregated LiFePO(4)-ACB grew to 250 nm at these conditions. Annealing at 800 °C induced carbothermal reduction of LiFePO(4) to Fe(2)P by ACB shell consumption that resulted in cavities between carbon shell and core LiFePO(4) and even slight LiFePO(4) crystal growth but better electrochemical performance. The present carbon-coated LiFePO(4) showed superior cycle stability and higher rate capability than the benchmark, commercially available LiFePO(4).